(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The present study was carried out to detect the prevalence of anaplasmosis in cattle at Rayganj and Ullahpara upazila in Sirajganj district of Bangladesh and to evaluate the therapeutic efficacy of traditional drugs like Oxetetracycline (Renamycine®), Imidocarb diproprionate (Babenil®) and Diminazine aceturate (Berenil®) against anaplasmosis in cattle. The study was conducted from July 2016 to December 2016. During six months of study period a total of 150 blood samples were collected from clinically ill and suspected cattle, among which 28 samples were positive for anaplasmosis by Geimsa stained blood smear method. It was observed that the overall prevalence of anaplasmosis in cattle was 18.67%, where 16.25% was Geimsa stained blood smear at Rayganj and 21.43% at Ullapara upazila respectively and the variation was not statistically significant (p>0.05). In respect of age the prevalence of anaplasmosis was significantly (p< 0.05) higher (31.7%) in 2-3 years of age group cattle than above 3 years (16.67%) and 6 months to 2 years age (10.20%) group. On the basis of sex, it was observed that the variation in prevalence in male (15.94%) and female (20.99%) was not statistically significant (p>0.05). Breed-wise prevalence was higher in crossbred cattle (19.5%) than local cattle (17.8%), was not statistically significant (p>0.05). It was observed that among three drugs used in this study, the best effectiveness of drugs was seen by Oxytetracycline (Renamycine LA®) @ 10 mg/kg body weight followed by Imidocarb dipropionate (Babenil®) @ 3.5 mg/kg body weight moderately and less by Diminazine aceturate (Berenil®) @ 3.5 mg/kg body weight. From the study it was evident that cattle were infected with the organisms and caused a heavy economic loss which recommended taking necessary preventive measurements. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 162-168